OPERATIONAL PERFORMANCE OF LAMPULO OCEANIC FISHING PORT BANDA ACEH NANGGROE ACEH DARUSSALAM PROVINCE - Novia Okta Sari; T.Ersti Yulika Sari; Ronald Mangasi Hutauruk (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTLampulo Oceanic Fishing Port is located in the city of Banda Aceh with fishing grounds in the Malacca Strait and the Indian Ocean, included in the Fisheries Management Area of the Republik of Indonesia 571 and 572. As one of the government agencies that plays an important role in supporting the development of capture fisheries in the city of Banda Aceh, then the port operational performance needs to be interpreted so that it can provide alternative solution to improve operational performance in the future so that it can provide more optimal services for the wearer. The problems at the Lampulo Oceanic Fishing Port so faris the low level of operation and service of the fishing port caused by internal and external factors at the fishing port.Therefore, this study was conducted to find out how much the operational performance level of the Lampulo Oceanic Fishing Port by looking at operational activities and fishermen satisfaction with port services as a basis for solving existing problems.The assessment of operational performance of the Lampulo Oceanic Fishing Port in analyzed using the Scorring Method which will then be analyzed descriptively.Based on the results of the analysis conducted showed that the operational performance of the Lampulo Oceanic Fishing Port is included in the quite good category with a value of 2,71 included in the interval (2,6-<3,4).Keyword: Fishing Port, Scorring Method, Operational Performance